Benefits of the speeking valve in tracheostomized children: an integrative review (Research, Society and Development, 2021)
Objectives: to develop an integrative review as a way to alert health professionals about the benefits of using the speech valve in tracheostomized children. Methods: The articles were searched in the online database MEDLINE (International Literature), LILACS (Latin American and Caribbean Health Sciences Information Literature) and SCIELO (Online Scientific Electronic Library) between January 2012 and March 2021 The following keywords were used: tracheostomy, child and “speech, language and hearing sciences”, extracted from Mesh/Decs, besides “passy-muir” and “speaking valve”. From the research, 37 articles were included, and after exclusions, a total of 11 articles that answered the guiding question. Results: after analyzing the data, several advantages were noted that the adaptation of the speech valve offers to tracheostomized children. Conclusion: It has been demonstrated in the literature the benefits that the speaking valve provides children in the rehabilitation process. The most cited were that it allows speech, improves swallowing, reduces secretion, accelerates decannulation, used in rehabilitation, can be used in mechanical ventilation and prevents infections. It was also observed restricted researches focused on children tracheostomized with the use of the speech valve.